Un viaggio verticale: Stratificazioni simboliche del mare nell’opera e nella biografia di Elsa Morante (TEST Ticontre. Theory Text Translation, 2022)
This study aims at analysing the figure of the sea in the life and artwork of Elsa Morante starting from the linguistic links to the marine space. The investigation explores both the semantic relation of the word with other terms, and in turn their correspondence by similarity or by contrast, and the association by images and concepts related to the sea. Starting from the consideration that Morante’s story develops by figure simmetries related to precise meanings within the text, we will attempt to identify the association network – both semantic and figurative- and the possible references hold by the sea “open space”.